Challenges and Responses: A Comparison of Management Dilemmas and Development Strategies of Public Libraries in China and the United States in Serving Digitally Disadvantaged Groups - Nan Liu (Journal of Frontier in Economic and Management Research, 2025)
This paper focuses on the service management for digitally disadvantaged groups in Chinese and American public libraries. Utilizing a comparative analysis method, it explores the differences and dilemmas between the two countries in terms of policy support, resource allocation, service models, and librarian training. The research finds that the United States has established a relatively comprehensive legal guarantee system and diverse funding channels, but recent federal policy fluctuations pose risks to project sustainability. Although China has made significant progress in equalizing services, it still faces structural challenges such as insufficient institutional guarantees and uneven resource allocation. Based on the comparative analysis, this paper proposes strategic suggestions including establishing a four-dimensional support system of "Law-Resources-Technology-Personnel" and promoting a "Digital Inclusion Partnership" model, aiming to provide references for Chinese public libraries to improve services for digitally disadvantaged groups.